Iatrogenic Cushing’s Syndrome Following Short-Term Intranasal Steroid Use - Dutta, Deep (Galenos Publishing, 2012)
Cushing’s syndrome (CS) is common after oral steroid use and has also been reported following topical or inhaled use, but it is extremely uncommon after intranasal administration. In this paper, we present the case of a child who developed CS after intranasal application of combined moxifloxacin-dexamethasone eye drops for epistaxis for a period of 3 months. CS caused by ocular preparations of steroids has not been reported previously. This case report highlights the fact that even eye drops can contain high doses of steroids and can lead to CS especially in children and especially if used intranasally. Ocular steroid drops should not be used intranasally. To minimize gastrointestinal absorption and therefore the risk of CS, nasal sprays should be preferred over nasal drops for intranasal steroid application.Key words: Cushing’s syndrome, eye drops, dexamethasone, epistaxis Conflict of interest:None declared.